Critical perspectives on agrarian transition: India in the global debate - Mohanty, Bibhuti Bhusan (Routledge, Taylor & Francis Group, 2016)
This book evaluates the relevance of classical debates on agrarian transition and extends the horizon of contemporary debates in the Indian context, linking national trends with regional experiences. It identifies new dynamics in agrarian political economy and presents a comprehensive account of diverse aspects of capitalist transition both at theoretical and empirical levels. The essays discuss several neglected domains in agricultural economics such as discursive dimensions of agrarian relations and limitations of stereotypical binaries between capital and non-capital, rural and urban sectors, agriculture and industry, and accumulation and subsistence. With contributions from major scholars in the field, this volume will be useful to scholars and researchers of agriculture, economics, political economy, sociology, rural development and development studies
Keywords: Konferenzschrift -- 2014 -- Pondicherry; Aufsatzsammlung; Strukturwandel; Landwirtschaft; Indien